KARAKTERISASI MINERAL ZEOLIT KECAMATAN GEDANGSARI DAN SEKITARNYA, KABUPATEN GUNUNGKIDUL, DAERAH ISTIMEWA YOGYAKARTA - Rinaldy Mesakh Kase (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2018)
Zeolite is a group of aluminosilicate mineral with several type of minerals as its member. Type of this zeolite mineral influenced the efficiency and effectiveness of its utilization. That thing also matter to group of zeolite mineral which is spread within Tegalrejo and the sorrounded area of Gedangsari Subdistrict, Gunungkidul Regency, Yogyakarta Special Region. Physical characterization of zeolite mineral including its physically appearance, crystalography and mineralogy. This physical characterization determined by several analysis including petrographic, XRD, and SEM analysis. Petrographic analysis done to understand texture and the group of mineral which is composed the sample, which is: tuffaceous mudstone, sandy tuff and tuffaceous sandstone. XRD and SEM analysis done to understand typical of mineral which composed the sample, in this case: mordenite and clinoptilolite type of zeolite; smectite; K-feldspar; plagioclase; and quartz. The result shows that type of zeolite minerals which occupied the sampling area were mordenite and clinoptilolite that distributed apportionment within the sample.